2020
DOI: 10.21203/rs.3.rs-40220/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poor Outcomes in Patients with Cirrhosis and COVID-19

Abstract: Abstract Background and AimThere is a paucity of data on the clinical presentations and outcomes of Coronavirus disease 2019(COVID-19) in patients with underlying liver disease. We aimed to summarize the presentations and outcomes of COVID-19 positive patients and compare with historical controls.MethodsPatients with known chronic liver disease who presented with superimposed COVID- 19(n=28) between 22nd April and 22nd June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[28,29] Of all the patients included in the present study, outcomes of 13 patients have been described in our previous publication. [1] A recent study from the United States reported outcomes of patients with COVID-19 pneumonia and GI bleed managed conservatively. [10] This study included 6 patients with likely ulcerrelated bleeding and mean GBS of 13.5.…”
Section: Outcomes Of Ugi Bleedmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,29] Of all the patients included in the present study, outcomes of 13 patients have been described in our previous publication. [1] A recent study from the United States reported outcomes of patients with COVID-19 pneumonia and GI bleed managed conservatively. [10] This study included 6 patients with likely ulcerrelated bleeding and mean GBS of 13.5.…”
Section: Outcomes Of Ugi Bleedmentioning
confidence: 99%
“…Recent data suggest that the overall prevalence of chronic liver disease (CLD) among COVID-19 patients is around 3-4%. [1] Patients with CLD and cirrhosis are at higher risk of mortality from COVID-19, especially those with acute-on-chronic liver failure. [1,2] The clinical presentation of COVID-19 in patients with CLD and cirrhosis, apart from respiratory symptoms, may include acute decompensation (AD) with gastrointestinal (GI) bleeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that the overall prevalence of chronic liver disease (CLD) among COVID-19 patients is around 3–4%. 1 Patients with CLD and cirrhosis are at higher risk of mortality from COVID-19, especially those with acute-on-chronic liver failure (ACLF). 1 , 2 The clinical presentation of COVID-19 in patients with CLD and cirrhosis, apart from respiratory symptoms, may include acute decompensation (AD) with gastrointestinal (GI) bleeding.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The clinical presentation of COVID-19 in patients with CLD and cirrhosis, apart from respiratory symptoms, may include acute decompensation (AD) with gastrointestinal (GI) bleeding. 1 …”
Section: Introductionmentioning
confidence: 99%